Bond strength of resin modified glass ionomer cement to primary dentin after cutting with different bur types and dentin conditioning - Di Nicolo, Rebeca [UNESP]; Shintome, Luciana Keiko [UNESP]; Myaki, Silvio Issao [UNESP]; Nagayassu, Marcos Paulo [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2007)
The aim of this in vitro study was to evaluate the effect of different bur types and acid etching protocols on the shear bond strength (SBS) of a resin modified glass ionomer cement (RM-GIC) to primary dentin. Forty-eight clinically sound human primary molars were selected and randomly assigned to four groups (n=12). In G1, the lingual surface of the teeth was cut with a carbide bur until a 2.0-mm-diameter dentin area was exposed, followed by the application of RM-GIC (Vitremer - 3M/ESPE) prepared according to the manufacturer's instructions. The specimens of G2, received the same treatment of G1, however the dentin was conditioned with phosphoric acid. In groups G3 and G4 the same procedures of G1 and G2 were conducted respectively, nevertheless dentin cutting was made with a diamond bur. The specimens were stored in distilled water at 37 degrees C for 24h, and then tested in a universal testing machine. SBS. data were submitted to 2-way ANOVA (= 5%) and indicated that SBS values of RM-GIC bonded to primary dentin cut with different burs were not statistically different, but the specimens that were conditioned with phosphoric acid presented SBS values significantly higher that those without conditioning. To observe micromorphologic characteristics of the effects of dentin surface cut by diamond or carbide rotary instruments and conditioners treatment, some specimens were examined by scanning electron microscopy. Smear layer was present in all specimens regardless of the type of rotary instrument used for dentin cutting, and specimens etched with phosphoric acid presented more effective removal of smear layer. It was concluded that SBS of a RM-GIC to primary dentin was affected by the acid conditioning but the bur type had no influence.
Keywords: glass ionomer cements; modified; dental instruments; dentin; prymary teeth; conditioning